Optimizing unit capacities for a wind‐hydrogen power system of clustered wind farms. (26th September 2018) - Jiang, Yuewen; Wen, Buying; Wang, Yanbin
Summary: In general, wind power output of clustering wind farms must be massively transmitted. The wind power in each wind farm is correlated, intermittent, fluctuant, and cannot be accommodated all the time, causing the intractable decision of economical transmission capacity of a project transmitting wind power to a power grid. Furthermore, the drastic fluctuation of clustered wind power results in enormous challenges regarding the safety of a power system. For these reasons, the concept of a wind‐hydrogen power system for clustered wind farms is proposed. Next, a multiobjective model for optimizing the capacities, including the transmission project, hydrogen‐producing system, and fuel cells, is constructed based on the joint distributed character of wind speed, which consists of maximizing social benefit and the qualified rate of smoothing clustering wind power fluctuations. Finally, a case is analyzed in detail, accounting for the wind volatility, wind curtailment probability, and the costs of both hydrogen production and the fuel cells.